1992
DOI: 10.1172/jci115563
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of xanthine dehydrogenase and xanthine oxidase activity and gene expression in cultured rat pulmonary endothelial cells.

Abstract: The central importance of xanthine dehydrogenase (XDH) and xanthine oxidase (XO) in the pathobiochemistry of a number of clinical disorders underscores the need for a comprehensive understanding of the regulation of their expression. This study was undertaken to examine the effects of cytokines on XDH/ XO activity and gene expression in pulmonary endothelial cells. The results indicate that IFN-'y is a potent inducer of XDH/XO activity in rat lung endothelial cells derived from both the microvasculature (LMVC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
67
1
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(74 citation statements)
references
References 35 publications
5
67
1
1
Order By: Relevance
“…We found that hypoxia-mediated XDH/XO activation is dependent on the JAK/ STAT pathway in primary cultures of LMVEC. We demonstrated that the XDH/XO activity significantly increased by hypoxia, consistent with the increased phosphorylation or activation of XDH/XO in response to hypoxia in other cells (Terada et al, 1992;Dupont et al, 1992;Kayyali et al, 2001;Mervaala et al, 2001;Terada et al, 1997;Poss et al, 1996;Sohn et al, 2003;Kang et al, 2006). Interestingly, our data demonstrated that XDH/XO activation induced by could be inhibited by either depletion of IL6 using IL6 antibodies, pretreatment with the JAK2 inhibitor AG490 or transient expression of the JAK-STAT pathway blocker SOCS3 and their inhibitory effect on the XDH/XO activation was at a similar magnitude.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We found that hypoxia-mediated XDH/XO activation is dependent on the JAK/ STAT pathway in primary cultures of LMVEC. We demonstrated that the XDH/XO activity significantly increased by hypoxia, consistent with the increased phosphorylation or activation of XDH/XO in response to hypoxia in other cells (Terada et al, 1992;Dupont et al, 1992;Kayyali et al, 2001;Mervaala et al, 2001;Terada et al, 1997;Poss et al, 1996;Sohn et al, 2003;Kang et al, 2006). Interestingly, our data demonstrated that XDH/XO activation induced by could be inhibited by either depletion of IL6 using IL6 antibodies, pretreatment with the JAK2 inhibitor AG490 or transient expression of the JAK-STAT pathway blocker SOCS3 and their inhibitory effect on the XDH/XO activation was at a similar magnitude.…”
Section: Discussionsupporting
confidence: 81%
“…It has been demonstrated that hypoxia activates XDH/XO, an important source of reactive oxygen species (ROS) (Terada et al, 1992;Dupont et al, 1992;Kayyali et al, 2001;Mervaala et al, 2001;Terada et al, 1997;Poss et al, 1996;Sohn et al, 2003;Kang et al, 2006). However, the molecular mechanism underlying the hypoxia-mediated activation of XDH/XO remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The immunohistochemical localization of increased XO in the vessel wall of SCD mice could be a manifestation of either the binding and uptake of circulating XO by vascular endothelial cells (33,50,51) or the increased expression of XOR by activated vascular endothelium (52). Considering the high association constant of XO for binding to vascular endothelium (K d 檄 6 nM; ref.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of XDH/XO is specifically induced by IFN-c in lung microvascular endothelial cells and the pulmonary artery endothelial cells. In contrast, IFN-a/b, TNF-a, IL-1 or -6, LPS, and PMA have no effect on the activity of XDH/XO (104). The activity of XO is up-regulated in the airway inflammatory disorders, ischemia reperfusion injury, atherosclerosis, diabetes, and autoimmune disorders such as rheumatoid arthritis (332).…”
Section: Xo-derived Ros In Inflammationmentioning
confidence: 96%